The Influence of Supportive Leadership Behavior and Organizational Support on The Job Satisfaction of Followers - Mala, Abdurrahman R; Abdullah, Abdul Haris; Nento, Shinta (JURNAL AL-TANZIM, 2022)
Supportive leadership is the hope of organizations that wish to be efficient and competitive in services. There is a positive perception of leadership that potentially increases the job satisfaction of members. To achieve job satisfaction under supportive leadership, other variables are needed in achieving goals, including organizational support by subordinates. Therefore, this study examines predictively supportive leadership on job satisfaction and organizational support as moderate variables. Data were obtained from two state Islamic higher education institutions in Indonesia with the unit of analysis being ASN employees as many as 75 respondents were obtained randomly as a sample. While the data were collected through google form, the analysis method was using Structural Equation Modeling (SEM) assisted by SmartPls 3.2 software. Research findings indicate that supportive leadership behavior has a major contribution to employee job satisfaction. However, perceived organizational support as a moderate variable on job satisfaction has a less significant contribution.